2012
DOI: 10.1021/es204094v
|View full text |Cite
|
Sign up to set email alerts
|

Stable Carbon Isotope Ratio Analysis of Anhydrosugars in Biomass Burning Aerosol Particles from Source Samples

Abstract: A new method for stable carbon isotope ratio analysis of anhydrosugars from biomass burning aerosol particle source filter samples was developed by employing Thermal Desorption--2 Dimensional Gas Chromatography--Isotope Ratio Mass Spectrometry (TD-2DGC-IRMS). Compound specific isotopic measurements of levoglucosan, mannosan, and galactosan performed by TD-2DGC-IRMS in a standard mixture show good agreement with isotopic measurements of the bulk anhydrosugars, carried out by Elemental Analyzer--Isotope Ratio Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 42 publications
(52 reference statements)
6
40
0
Order By: Relevance
“…Fine fraction particles predominately consist of OM (Organic Matter) (Bressi et al, 2013); thus, organic carbon from traffic emissions can lead to the lower δ 13 C TC values in fine fraction particles, particularly during autumn-winter time in urban areas. Coarse fraction particles had more positive δ 13 C TC values in this study than the fine fraction particles, thus having a good agreement with reported data (Cachier et al, 1985;Garbaras et al, 2009;Sang et al, 2012). The enrichment in 13 C of the coarse particles can be a result of contribution of carbonates that come from a variety of sources in urban areas: rural soils, street and non-paved road dust (Lopez-Veneroni, 2009;Manoli et al, 2002), and construction activities (e.g., re-suspension of mineral dust) (Dimitriou and Kassomenos, 2014;Keuken et al, 2013).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Fine fraction particles predominately consist of OM (Organic Matter) (Bressi et al, 2013); thus, organic carbon from traffic emissions can lead to the lower δ 13 C TC values in fine fraction particles, particularly during autumn-winter time in urban areas. Coarse fraction particles had more positive δ 13 C TC values in this study than the fine fraction particles, thus having a good agreement with reported data (Cachier et al, 1985;Garbaras et al, 2009;Sang et al, 2012). The enrichment in 13 C of the coarse particles can be a result of contribution of carbonates that come from a variety of sources in urban areas: rural soils, street and non-paved road dust (Lopez-Veneroni, 2009;Manoli et al, 2002), and construction activities (e.g., re-suspension of mineral dust) (Dimitriou and Kassomenos, 2014;Keuken et al, 2013).…”
Section: Resultssupporting
confidence: 89%
“…Cascade impactors were used to study fine particulate matter in numerous studies (Cabada et al, 2004;Chow et al, 2008;Fang et al, 2006;Huang et al, 2004;Yao et al, 2001;Keywood et al, 1999;Kleeman et al, 2008;Liu et al, 2008;Lü et al, 2012;Plaza et al, 2011;Singh et al, 2003); however, only a few of them attempted to study stable carbon isotope ratio values (Cachier et al, 1985;Garbaras et al, 2009;Sang et al, 2012;Wang et al, 2012) that are a useful tool to identify the sources of particulate matter. Furthermore, δ 13 C TC values can provide a useful starting point in detecting and distinguishing carbonaceous aerosol particles.…”
Section: Introductionmentioning
confidence: 99%
“…The composition of anhydrosugars (Gal, Man, and Lev) provides diagnostic information regarding the type of biomass (Sang et al, 2012). In this study, anhydrosugars were composed primarily of Lev (92% ± 0.6%), with the rest being Man (5% ± 0.5%) and Gal (3% ± 0.2%).…”
Section: Secondary Organic Carbon: Non-fossil Versus Fossil Sourcesmentioning
confidence: 68%
“…(OC/Lev) bb ratios vary with different biomass types (hardwood, softwood, and annual plants, such as grass) (SI Table S2) due to differences in cellulose content. On the basis of the ratios of the three anhydrosugar isomers, 28 biomass-burning aerosols in Guangzhou mainly originate from hardwood combustion (SI Table S2). Therefore, an (OC/Lev) bb ratio of 7.76 ± 1.47 (SI Table S2) was used to calculate OC bb in this study.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In this work, different carbon species (WIOC, WSOC, and EC) and water-soluble ions were measured, as well as three anhydrosugar isomers, i.e., levoglucosan (Lev), galactosan (Gal), and mannosan (Man), which are good markers of aerosols derived from biomass burning. 27,28 Eight samples representing different atmospheric conditions were selected to further analyze the 14 C content of WIOC, WSOC, and EC, as well as secondary organic aerosol (SOA) tracers that could directly reflect atmospheric reactions.…”
Section: ■ Introductionmentioning
confidence: 99%